2020
DOI: 10.1186/s12931-020-01421-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends and seasonal variation of hospitalization and mortality of interstitial lung disease in the United States from 2006 to 2016

Abstract: Background: In the recent years, the overall trends in hospital admission and mortality of interstitial lung disease (ILD) are unknown. In addition, there was some evidence that interstitial lung disease death rate highest in the winter but this finding was only available in one study. This study will investigate the trend and seasonal variations in hospital admission and mortality rates of ILD from 2006 to 2016. Method: From the Nationwide Inpatient Sample database, we collected all cases with the Internation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…These findings stand in contrast to those published using the online CDC national death certificate database, which showed IPF-related mortality to be increasing over this timeframe [ 31 , 32 ]. Besides, others reported decline in IPF all-cause mortality and hospitalizations using NIS dataset [ 33 ]. With different case finding methodologies employed by each study, these observations highlight the difficulties with capturing accurate IPF data using claims databases.…”
Section: Discussionmentioning
confidence: 99%
“…These findings stand in contrast to those published using the online CDC national death certificate database, which showed IPF-related mortality to be increasing over this timeframe [ 31 , 32 ]. Besides, others reported decline in IPF all-cause mortality and hospitalizations using NIS dataset [ 33 ]. With different case finding methodologies employed by each study, these observations highlight the difficulties with capturing accurate IPF data using claims databases.…”
Section: Discussionmentioning
confidence: 99%
“…There was a stark increase in ECI from August until October, followed by a sudden decline in the latter part of the year. Since winter months see a higher hospitalization rate [ 19 ], and another study has shown a similar pattern in admission months for patients with pneumonia across hospitals [ 20 ], then a possible reason for under-coding could be the increased workload on hospital staff, resulting in exhaustion, under-documentation, and under-coding.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Besides, others reported decline in IPF all-cause mortality and hospitalizations using NIS dataset. [33] With different case nding methodologies employed by each study, these observations highlight the di culties with capturing accurate IPF data using claims databases.…”
Section: Discussionmentioning
confidence: 99%